2022
DOI: 10.1039/d2cp02866b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of imidazolium-based ionic liquids with supported phospholipid bilayers as model biomembranes

Abstract: The cytotoxicity of Ionic Liquids (ILs) has been raising attention in the context of the biological and environmental impact of their vast field of applications. It is ascertained that the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…In the case of C 12 MIm (CF 3 SO 2 ) 2 N), segregated IL droplets were observed at the bilayer surface at concentrations near the IL CMC, which, in turn, led to fast formation of multilayer structures. 350 Among the imidazolium ILs C n MIm Cl (n = 4, 8, 10), C 4 MIm BF 4 , and C 4 MIm (CF 3 SO 2 ) 2 N, the ILs with a short alkyl side chain and a hydrophilic anion induced mild disorder in supported lipid vesicles (SVLs) composed of DMPC, whereas the ILs with long alkyl side chains penetrated SLVs and disrupted them, forming a rigid supported lipid bilayer. The effect depended on the IL concentration, the length of the alkyl side chain in the cation, and the anion hydrophobicity.…”
Section: Interactions With Separate Cellular Organelles and Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of C 12 MIm (CF 3 SO 2 ) 2 N), segregated IL droplets were observed at the bilayer surface at concentrations near the IL CMC, which, in turn, led to fast formation of multilayer structures. 350 Among the imidazolium ILs C n MIm Cl (n = 4, 8, 10), C 4 MIm BF 4 , and C 4 MIm (CF 3 SO 2 ) 2 N, the ILs with a short alkyl side chain and a hydrophilic anion induced mild disorder in supported lipid vesicles (SVLs) composed of DMPC, whereas the ILs with long alkyl side chains penetrated SLVs and disrupted them, forming a rigid supported lipid bilayer. The effect depended on the IL concentration, the length of the alkyl side chain in the cation, and the anion hydrophobicity.…”
Section: Interactions With Separate Cellular Organelles and Moleculesmentioning
confidence: 99%
“…The affinity between this side chain and hydrophobic tails of the phospholipids presumably led first to accumulation of the IL cations on the bilayer surface and then to tail-first penetration of the cations into the bilayer, resulting in mechanical and structural weakening and, finally, disruption. In the case of C 12 MIm (CF 3 SO 2 ) 2 N), segregated IL droplets were observed at the bilayer surface at concentrations near the IL CMC, which, in turn, led to fast formation of multilayer structures …”
Section: Mechanisms Of Biological Activity Of Ionic Liquids: State Of...mentioning
confidence: 99%
“…Galluzzi et al demonstrated that the length of the alkyl chain of the IL cation dominated the strength of the IL and lipid bilayer interaction and observed the interaction between lipid bilayers deposited on mica surfaces and ILs through atomic force microscopy. 146 An experiment revealed that 1-hexyl-3-methylimidazolium acetate ([HMIM][OAc]) could be inserted into the lipid bilayer in the gel state, causing a more marked influence on the lipid bilayer than 1-butyl-3-methylimidazolium acetate ([BMIM][OAc]). 147 The permeation of the IL cation into the lipid membrane led to the reorganization and softening of the bilayer, ultimately forming an IL/lipid complex.…”
Section: Therapeutic Mechanismsmentioning
confidence: 99%
“…AFM analysis indicated the modification of the charge density of a bilayer due to the crowding cations of ILs. 48 Few reports suggested that the insertion of ILs in lipid membranes alters the alkyl chains of lipids relatively more than the polar head group region. 17,20,49−52 Further, the double-chained ILs are relatively less toxic than single-and long-chain ILs.…”
Section: Introductionmentioning
confidence: 99%
“…ILs might interact with a membrane through electrostatic and hydrophobic interactions, which may depend on the charge and hydrophobicity of both the lipids and ILs. , Imidazolium-based ILs reduce the mechanical stability of a supported DOPC lipid bilayer formed on a mica substrate. AFM analysis indicated the modification of the charge density of a bilayer due to the crowding cations of ILs . Few reports suggested that the insertion of ILs in lipid membranes alters the alkyl chains of lipids relatively more than the polar head group region. ,, Further, the double-chained ILs are relatively less toxic than single- and long-chain ILs. , …”
Section: Introductionmentioning
confidence: 99%